Effects of an educational compact intervention in self-care: a mixed methods study with postgraduate trainees in primary care - Schwill, Simon; Bugaj, Till Johannes; Rentschler, Annalena; Nikendei, Christoph; Szecsenyi, Joachim; Krug, Katja (BMC primary care, 2023)
Multiple studies indicate that residents in family medicine (FM) are exposed to considerable stress and are particularly affected by burnout syndrome. Aim of the study was to specify the effects of a so-called “compact intervention” (i.e., a short intervention) in self-care on FM residents.
Gesehen am 17.08.2023